Os usos do conceito de cultura africana e afro-brasileira nos livros didáticos de história para o ensino médio - PNLD 2012 - Sodré, Rylton Marcus Alves (2018)
The present research aims to identify and analyze the uses of the concept of african and afro-brazilian culture in the textbooks of History for High School - PNLD 2012. As a methodological procedure, the Bibliographic Research was used, performing the critical reading for the (2010), History of the caves to the third millennium (2010) and New Integrated History (2010), mapping the theoretical and bibliographic references adopted by the authors of the works when approaching the concept of culture - based on the discussion about African and afro-brazilian themes, also seeking to identify the permanences and cultural changes in textbooks about african and afro-brazilian societies. The results of the research make it possible to demonstrate that the african peoples in the pages of the same ones still receive stereotyped treatments, although at times they present actions to eliminate the stereotypes of the representation of afro groups as participants in the sociocultural and economic process in society brazilian.